2011
DOI: 10.1016/j.jmoldx.2010.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Deletions of EPCAM (TACSTD1) in MSH2-Associated Lynch Syndrome Cases

Abstract: Lynch syndrome is an autosomal dominant cancer predisposition syndrome characterized by loss of function of DNA mismatch repair enzyme MLH1, MSH2, MSH6, or PMS2. Mutations in MLH1 and MSH2 account for ϳ80% of the inherited cases. However, in up to 20% of cases suspected of having a germline mutation in MSH2 due to loss of MSH2 expression, a germline mutation is not identified. Recent studies have shown that some Lynch syndrome cases are due to 3= EPCAM/TACSTD1 deletions that subsequently lead to MSH2 promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 41 publications
5
52
0
Order By: Relevance
“…Tumors arising from EpCAM gene deletion demonstrate an MSI-high profile and loss of MSH2 and/or MSH6 by IHC. 76,77 Deletions in the 3′ region of the EpCAM gene can be detected using Southern blot, MLPA, or gene-targeted aCGH and should be analyzed in patients with IHC results showing loss of MSH2 and/or MSH6.…”
Section: Epcam Deletionmentioning
confidence: 99%
“…Tumors arising from EpCAM gene deletion demonstrate an MSI-high profile and loss of MSH2 and/or MSH6 by IHC. 76,77 Deletions in the 3′ region of the EpCAM gene can be detected using Southern blot, MLPA, or gene-targeted aCGH and should be analyzed in patients with IHC results showing loss of MSH2 and/or MSH6.…”
Section: Epcam Deletionmentioning
confidence: 99%
“…9 EPCAM deletions lead to a transcriptional read-through, silencing MSH2 9 and are estimated to cause Lynch syndrome in B20-25% of patients with MSH2-negative cancers, but no detectable MSH2 germline mutation. 10 This corresponds to B2-3% of Lynch syndrome patients. 10 A recent study demonstrated that concomitant lack of EPCAM and MSH2 protein expression is a feature highly specific for cancers from EPCAM deletion carriers, suggesting EPCAM immunohistochemistry as a potential tool for the identification of Lynch syndrome patients with EPCAM germline deletions.…”
mentioning
confidence: 99%
“…10 This corresponds to B2-3% of Lynch syndrome patients. 10 A recent study demonstrated that concomitant lack of EPCAM and MSH2 protein expression is a feature highly specific for cancers from EPCAM deletion carriers, suggesting EPCAM immunohistochemistry as a potential tool for the identification of Lynch syndrome patients with EPCAM germline deletions. 11 However, EPCAM protein expression was retained in some cancers from EPCAM deletion carriers.…”
mentioning
confidence: 99%
“…[70][71][72] EPCAM (also known as TACSTD1) deletion leading to MSH2 promoter methylation is another common genetic aberration causing Lynch syndrome. [73][74][75] Therefore, it is evident that only a proportion of hereditary non-polyposis colorectal cancer cases which fulfill the Amsterdam Criteria have germline mutations in mismatch-repair genes, which by 'definition' constitutes Lynch syndrome. As a result, families with a strong family history of colorectal cancer that do not have Lynch syndrome have been grouped as 'familial colorectal cancer-type X'; alternatively, some studies have referred to them as mismatch-repair gene mutation-positive and -negative families for Lynch syndrome and familial colorectal cancer type X, respectively.…”
Section: Familial Colorectal Cancer Type X Is Distinct From Lynch Synmentioning
confidence: 99%